Implementasi Pembelajaran Kontekstual berpendekatan Learning Community pada Bidang Studi Fiqh dalam Meningkatkan Motivasi dan Prestasi Belajar Siswa MI Mambaul Hidayah Mengelo Sooko Mojokerto - Mas’adah (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
Education is a conscious and systematic effort not only to humanize human beings but also for human beings to realize their position as khalifatullah fil ardhi, which in turn will increasingly increase itself to be a pious, faithful, knowledgeable and virtuous man. In general the problems formulated in this research is whether Implementation of Contextual Learning with Learning Community approach can improve student's motivation and achievement in FIQH study field? How Implementation of Contextual Learning has a Learning Community approach that can improve students' motivation and achievement in FIQH? Field. This research was conducted in Mojokerto Regency, precisely at MI Mambaul Hidayah Mengelo Sooko Mojokerto. This research is a classroom action research with collaborative type. This research phase follows a model developed by Kemmis and Taggart, which is a spiral cycle that includes planning activities, action execution, observation, and reflection. The data collection techniques used are: (1) observation; (2) measurement of learning result test; and (3) documentation. Data obtained from the action are then analyzed. Qualitative data consisting of observation and documentation are analyzed qualitatively, while data collected in the form of numbers or quantitative data, simply by using descriptive analysis and visual presentation. Based on the results of research that has been implemented can be concluded that the Implementation of Contextual Learning with Learning Community approach can improve student's motivation and achievement in the field of FIQH study. From the data in the field shows that there is an increase in student learning motivation that the initial average value of pre-test of 20 increased to 24 or about 20% in cycle I, in cycle II more increased to 31 or about 55%, and in cycle III the more increased to 45 or about 125%. Level of increase between cycle I with cycle II about 29%, between cycle II with cycle III about 45%, between cycle III with cycle I about 87%. With the increase of students' learning motivation, their learning achievement also increased, whereas the average value of pre test of 6.60 increased to 6.84 or about 4% in cycle I, in cycle II more increased again to 7.75 or about 17 %, and in cycle III it increases to 8.80 or about 35%. The level of improvement between cycle I with cycle II is about 13%, between cycle II with cycle III about 15%, between cycle III with cycle I about 30%.